Analisis Kepatuhan Pekerja Terhadap Penggunaan Alat Pelindung Diri - Erlina Marbun (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Personal protective equipment (PPE) is equipment that must be used in the workplace so that workers avoid risk factors for work accidents and occupational diseases. However, even though PPE has been provided and its use is regulated, there is still frequent non-compliance by workers with the use of PPE, so training and supervision of the use of PPE while working is needed. This study focuses on the use of PPE by workers at the Sawit Seberang Palm Oil Mill (PKS). This study is a qualitative study with a case study research design, has comprehensive data collection and involves various sources of information. The purpose of this study is to analyze the level of worker compliance with guidelines for the use of PPE in the work environment. From the results of the analysis that has been carried out previously, the frequency of PPE use shows that 80% of workers at PTPN -II Operational PKS Sawit Seberang comply and use PPE routinely and regularly, but there are still a small number of workers who do not use PPE, namely 20% of workers at PTPN-II Operational PKS Sawit Seberang do not comply or do not routinely use PPE, this can potentially interfere with performance. Therefore, it is necessary to make improvement efforts such as creating a supervision and training schedule that can improve workers' understanding of the importance of using PPE while working for the health and safety of workers at PT. Perkebunan Nusantara II PKS Sawit Seberang Operation. Further research is needed regarding workers' compliance with the use of PPE.